Changes in the System of Oblique Cases in Molise Croatian Dialect - Peša Matracki, Ivica (Array, 2013)
The linguistic situation in Molise Croatian dialect is characterised by absolute language contact in which the borrowings from the adstrate and superstrate Romance varieties are so numerous that the Molise Croatian linguistic community is threatened with extinction. From this perspective of language decay we will try to examine the changes of the morphological features of cases and verb phrases modified by indirect objects in an oblique case (genitive, dative and instrumental case). The direct and indirect objects are noun phrases which are a part of a verb phrase, i.e. they are complements required by the thematic structure of the verb. In our discussion we will describe the main changes in the system of inflection of the oblique cases in Molise Croatian (including the role of case markers), and examine their different syntactic and semantic characteristics. Special attention will be paid to the causes of the weakening of the inflection system as well as on those factors which, on the other hand, help maintain the strength of the inflection system which, although with forms and structures which greatly differ from the original ones, continues to function in Molise Croatian dialect.